Lanthanum Inhibits Primary Root Growth by Repressing Auxin Carrier Abundances in Arabidopsis - Liu, Yangyang; Sun, Liangliang; Zhang, Ping; Wan, Jinpeng; Wang, Ruling; Xu, Jin (Frontiers in Plant Science, 2017)
LLanthanum (La) is one of rare earth elements that was used as a crop growth stimulants, however, high concentration of La markedly inhibited plant growth. Our previous study indicated that, although La induced the expression of auxin biosynthesis-related genes, it markedly repressed primary root (PR) elongation by reducing auxin accumulation in PR tips. In this study, we exhibited that La reduces the abundances of auxin carriers. Treatment with La markedly inhibited the auxins IAA-, 2,4-D-, and NAA-induced elevation of DR5:GUS activity in the roots, suggesting that La inhibited auxin transport through both the influx and efflux transporters. Supplementation with auxin transport inhibitor naphthylphthalamic acid (NPA) in La-treated seedlings did not further reduce PR growth compared with that of the La treatment alone, further confirmed that auxin transport is involved in La-induced inhibition of PR growth. Analysis of the protein abundances using the transgenic AUX1-YFP and PIN1/2/4/7-GFP marker lines indicated that La treatment reduced the abundances of all these auxin carriers in the PR tips. La also increased the stabilization of Aux/IAA protein AXR3. Taken together, these results indicated that La treatment inhibits PIN-mediated auxin transport and subsequently impairs auxin distribution and PR growth via reducing auxin carrier abundances.